Processing speed mediates the association between physical activity and executive functioning in elderly adults - Silva-Fernandes, Anabela; Cruz, Sara; Moreira, Célia Sofia; Pereira, Diana R.; Sousa, Sónia S.; Sampaio, Adriana; Carvalho, Joana (Frontiers in Psychology, 2022)
Advanced aging is associated with cognitive decline. To decrease the healthcare system and socio-economic burdens as well as to promote better quality of life, is important to uncover the factors that may be related to the delay of cognitive impairments in older adults. This study investigated the relationship between physical activity levels, sedentary behavior and cardiorespiratory fitness with cognitive functioning in healthy older adults. Furthermore, it examined the mediating role of processing speed on the association between physical activity and executive functions and long-term memory. Thirty-two individuals aged between 63 and 77 years (M=68.16, SD=3.73) underwent measurements of maximal oxygen uptake (VO2peak), 1-week of PA accelerometer measurement and a comprehensive cognitive assessment. Significant associations were observed between MVPA and cognitive processing speed. Equally, a significant positive indirect effect of MVPA on executive functioning and long-term memory was mediated by processing speed. Also, MVPA levels differentiated cognitive functioning in older adults – the physical active group outperformed the physical inactive group in processing speed, executive functions, and language abilities. Our results contribute to the literature on the MVPA levels as an important tool to promote healthier cognitive aging.